PERBAIKAN SIKAP KERJA DAN PENAMBAHAN PENERANGAN LOKAL PADA PROSES PEMBUBUTAN MENURUNKAN KELUHAN MUSKULOSKELETAL, KELELAHAN MATA DAN MENINGKATKAN KETELITIAN HASIL KERJA MAHASISWA DI BENGKEL MEKANIK POLITEKNIK NEGERI BALI - Pujihadi, Gede Oka; Adiatmika, Putu Gede; Tirtayasa, I Ketut (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 1 No 2 (2015): Volume 1 No 2 Desember 2015DO - 10.24843/JEI.2015.v01.i02.p01)
Practice of turning is done in a standing posture. During the process of turning benches are not provided for sitting. In turning Practice sometimes also requires bending forward working posture to look more carefully or repair existing equipment. Besides, the lack of site lighting on the lathe machine can reduce accuracy level of students in reading measurement scale. This leads to disorder on musculoskeletal system and eye strain; therefore it is necessary to apply ergonomics in terms of improvement in working posture and the addition of site lighting.The research was carried out experimentally using treatment by subject design; the study sample included 15 people. Subjects obtained the two treatments, period I the turning used the old way. Period II used a new way of ergonomic interventions in the form of improvement in working posture and the addition of site lighting.The analysis showed that there was significant difference (p <0.05) on the musculoskeletal disorder, the period I with a mean score of 81.41 +1.80 and atperiod II with a mean score of 65.74 +3.08 or decreased by 19.3 %. There was significant difference in eye strain period I with a score of 31.41 +1.78 and period II with a score of 16.89 +2.32 or decreased by 46.2% and there was significant difference in the accuracy of the work, period I with a bias score of 1.29 +0.45 cm and period II with a bias score of 0.56 +0.15 cm or increased accuracy of 56.9%.It is concluded that (a) the improvement of working posture and addition of site lighting in turning process can reduce musculoskeletal disorder of students in mechanical workshop of Bali State Polytechnics, (b) the improvement of working posture and addition of site lighting turning process can reduce eye strain of students in mechanical workshop of Bali State Polytechnic, (c) the improvement of working posture and addition of site lighting in turning process can improve the accuracy of the work of students in Bali State Polytechnic mechanical workshop.
Keywords: Improvement in working posture, site lighting, musculoskeletal disorder (MSD’s), eye strain, accuracy of work